ALIH FUNGSI LAHAN PERBUKITAN DALAM NOVEL TAHUN PENUH GULMA KARYA SIDDHARTHA SARMA - Tengku Zafira Maharani; Kurniawan, Eva Dwi (CV. Kalimasada Group, 2023)
Land conversion is one of the problems in environmental issues. Various problems need to be studied in an effort to provide solutions and recommendations. The issue of land conversion is also found in literary works. This research aims to see how land functions, the factors and impacts of the conversion of hilly land contained in the novel Tahun Full of Weeds by Siddharta Sarma. The method used uses a hermeneutical approach. The results obtained show that the functional form of hilly land becomes mining land, the causal factor is the capitalist system, and the impacts are in the form of population movement and damage to the environmental ecosystem..